Pola Komunikasi Antarbudaya Pada Masyarakat Berbeda Agama dalam Membentuk Solidaritas Sosial Masyarakat di Desa Sumberjati - Nur Diana Kholidah; Siti Raudhatul Jannah (Fakultas Dakwah UIN KHAS Jember, 2022)
Cultural and religious diversity in society can be marked by the differences that exist in an area, both differences in religion, habits or ways of communicating. The existence this difference can be seen how the interactions, ways of appreciating and respecting are carried out fellow communities in order create a harmonious life and uphold tolerance. Sumberjati Village is a village where the community has different religious beliefs, besides that differences are used as a community as a means to be able to build common goals and create a life of solidarity, namely harmony and peace. Study focuses: 1) What are the communication patterns used by people of different religions in uniting common goals in Sumberjati Village to form Social Solidarity? 2) How to respect and tolerate between Muslim and Catholic communities in Sumberjati Village form social solidarity? This research uses qualitative research methods descriptive approach. Methods of data collection using: observation, interviews, documentation. Data analysis: field analysis, namely data collection, data reduction, data presentation and conclusion drawing. For the validity of the data using source triangulation. Results study the communication patterns used by people different religions in Sumberjati Village, namely using primary and circular communication patterns. Communication patterns used are well established and effective in maintaining relations between the people they can respect each other about differences from different beliefs and cultures, these differences do not make them conflict or conflict with each other, but instead make them respect each other more as God's creatures and can tolerate.